Distal pancreatectomy with en bloc celiac axis resection (DP-CAR) using retroperitoneal-first laparoscopic approach (Retlap): A novel minimally invasive approach for determining resectability and achieving tumor-free resection margins of locally advanced pancreatic body cancer. (December 2022) - Kiguchi, Gozo; Sugioka, Atsushi; Uchida, Yuichiro; Mii, Satoshi; Kojima, Masayuki; Takahara, Takeshi; Kato, Yutaro; Suda, Koichi; Uyama, Ichiro
Abstract: Background: Conventional open distal pancreatectomy with en bloc celiac axis resection (DP-CAR) using the ventral approach is technically challenging, highly invasive, and not easy to ensure ample dorsal surgical margins. Hence, we describe a novel minimally invasive strategy for DP-CAR using the retroperitoneal-first laparoscopic approach (Retlap), i.e., Retlap DP-CAR, for locally advanced pancreatic body cancer (LAPC), and assess its utility. Methods: Retlap DP-CAR was performed in 10 patients with LAPC that was categorized as either unresectable (UR-LA, n = 4) or borderline (BR-A, n = 6). Neoadjuvant chemotherapy was applied on 8 patients and upfront surgery on 2. Retlap was used to create a working space in the retroperitoneal cavity between the pancreatic body and the left kidney and confirm technical resectability, such as securing the celiac axis and preserving the superior mesenteric artery in an early operative stage. Retlap DP-CAR was laparoscopic in 8 patients and robotic in 2. Surgical procedures are directly manipulated from the dorsal side of the pancreas and tumor, facilitating confirmation of technical resectability and obtaining ample dorsal margins in a no-touch isolation approach. Once technical resectability was confirmed, the procedure was converted to the ventral approach for completing DP-CAR. Results: Median operating time and blood loss during Retlap were 271 min and 10 mL, respectively, while median resection time and intraoperative blood loss were 582 min and 412 mL, respectively. Tumor-free resection margins were obtained in all cases. The major morbidity rate (C-D > IIIa) was 10%. No mortality was recorded within 90 days. Median overall survival was 53.8 months [95% confidence interval 32.7–75.0]. Conclusions: Retlap DP-CAR is a novel minimally invasive procedure for resecting LAPC located close to the celiac axis. It is both safe and feasible, enables determination of technical resectability, achieves dorsal surgical margins, and can improve outcomes and QOL in patients with LAPC. Highlights: Conventional open distal pancreatectomy with en bloc celiac axis resection (DP-CAR) is technically challenging. A novel minimally invasive strategy for DP-CAR using the retroperitoneal-first laparoscopic approach (Retlap) was developed. Retlap DP-CAR was performed in 10 patients with pancreatic body cancer, including 4 cases evaluated as unresectable-locally advanced. Retlap DP-CAR enabled determination of technical resectability and achieved tumor-free resection margins in all 10 cases. The major morbidity rate was 10%, with no mortality, and median overall survival was 53.8 months.